THE EXTENT OF USING MODERN TECHNOLOGY IN TEACHING METHODS - Wadiyan Hassan Ali (Journal of Social Science, 2026)
Objective: This research highlights the impact of integrating modern technology, specifically Artificial Intelligence (AI) and interactive learning tools, into teaching methods, and their direct role in elevating the quality of higher education. The research problem stems from the continued reliance on classical methods and theoretical indoctrination, which creates a comprehension gap and diminishes student motivation, in addition to addressing the challenges of teaching staff shortages. The research aims to emphasize the inevitability of transitioning towards interactive learning environments based on the "competency-based approach." Method: It reviews advanced technological applications, including smart classrooms, neural networks for analyzing classroom data, interactive screens, e-books, and the utilization of interactive videos within the "flipped classroom" model. Results: The research reached several key conclusions, most notably that employing these technologies does not eliminate the professor's role but rather reshapes it into that of a guide and mentor. It radically contributes to enhancing critical thinking and increasing the learner's independence and self-regulation. Novelty: The research recommends the necessity of building a smart, centralized network system within universities, mainstreaming the use of interactive screens, and training academic staff on the strategic design of digital content to ensure an active partnership between the professor and the student in managing and developing the educational process.